ANALYSIS OF CRISIS MANAGEMENT OF THE ENTERPRISE IN THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2017)
The oil and gas industry is the major and fastest developing industry in Kazakhstan. Kazakhstan is an important natural resources supply in national energy market and one of the largest countries in the world on stocks of hydro carbonic raw materials. In Kazakhstan 3.2% of world reserves of oil and 1.5% of gas is concentrated. The annual product of oil gets to 80 million ton per year, four tons for every citizen of Kazakhstan. The revenue from oil and gas, accounts for a significant part of Kazakhstan’s total GDP, its government budget and foreign trade income from export. When oil price in international market began to decline, the Kazakhstan government had to change its annual budget accordingly based on the oil price.Because of the reasons mentioned above the role of oil industry and especially enterprises became very important. In the current article we tried to find the best solutions how to efficiently manage an enterprise during the crisis.